Pleistocene environmental change through lake-level change - Charles, Bukho (https://orcid.org/0000-0002-9544-7678) (Rhodes University, 2026)
The Turkana Basin, Omo Group, in northern Kenya, has been a region of numerous palaeontological, archaeological, and geological investigations in eastern Africa due to its recognised prehistoric repository of biotic evolution, cultural history, and rift valley geology. These significant records are archived by the Plio-Pleistocene volcaniclastic deposits of the Koobi Fora Formation, which includes one of the eight consequential stratigraphy intervals, the Kay Behrensmeyer Site (KBS) Member time-interval deposits. Numerous palaeontological, archaeological, and geological research have been conducted in these deposits; however, there have been limited investigations in understanding source areas, punctuation, and influence of the palaeoenvironmental change in relation to noted lake level fluctuations and how they drove biotic evolution (including hominin adaptation). This study investigates the palaeoenvironmental dynamics of the KBS Member that have shaped its observed stratigraphic succession. This geological study provides comprehensive basin analysis, grounded in extensive fieldwork, through depositional lithofacies and palaeoenvironmental distribution across the KBS Member in space, offering a more detailed palaeogeographical interpretation. The research identifies extensive palaeoenvironmental heterogeneity across the formation’s three subregions, with a significant predominance of meandering fluvial channel patterns defined by distributive fluvial systems. Additionally, the sandstones are derived from two primary source rocks: The basement Precambrian Ethiopian outcrops east of the basin; The Kenyan Cenozoic volcano-sedimentary rocks extending north of the basin. Furthermore, with the adoption of sequence stratigraphic modelling, two parasequences that reflect two low-frequency transgressive-regressive cycles are established; this revealed that the origins of these fluctuations primarily originate from climatic-related factors with some tectonic- and volcanic-related forcings. This suggests that ancient Lake Turkana (Paleolake Lorenyang, 2–1.6 Ma) expanded asynchronously in the rift, resulting in variable depositional slopes in times of flooding. The study integrates sedimentary facies analysis and provenance studies to provide a better understanding of the depositional history and stratigraphic controls in the basin. This study contributes to existing work on the region, offering understanding of biotic evolution and the adaptive strategies of organisms (including hominins) in response to changing environmental conditions during the Pleistocene epoch.
sequence stratigraphic modelling of the KBS member, Koobi fora formation, OMO group
Keywords: Sediments (Geology) (http://id.loc.gov/authorities/subjects/sh85119509); Paleogeography (http://id.loc.gov/authorities/subjects/sh85097061); Sequence stratigraphy (http://id.loc.gov/authorities/subjects/sh2001004460); Geology; Facies analysis (https://www.wikidata.org/wiki/Q12568157); Koobi Fora Formation (https://www.wikidata.org/wiki/Q75038896); Palaeoenvironment (https://www.wikidata.org/wiki/Q136498382); Turkana Basin (https://www.wikidata.org/wiki/Q7855016)